Sistem Informasi Persediaan Obat Pada PT Mega Esa Farma Dengan Metode Extreme Programming - Rudianto, Biktra; Prisscilya, Sheren (Computer Science (CO-SCIENCE), 2025)
PT. Mega Esa Farma is one of the leading pharmaceutical companies in Indonesia, facing significant challenges in managing inventory information. The main issues lie in recording incoming and outgoing goods, final stock, and other inventory-related problems. These obstacles result in slow data processing and delays in providing accurate information, ultimately hindering the efficiency of product sales and distribution. This study aims to develop a web-based inventory information system capable of efficiently managing, processing, organizing, and storing data, while presenting accurate and real-time information. The system development adopts the Extreme Programming (XP) methodology, which emphasizes short iterations, automated testing, simple design, and close collaboration between users and developers. System analysis is carried out using the Unified Modeling Language (UML) to visualize the structure and functionality of the system. The implementation results show that the developed system simplifies inventory recording, accelerates information access, and improves data accuracy. It also provides features such as minimum stock notifications and real-time reporting, which were not available in the previous manual system. The main contribution of this study lies in applying the XP methodology in the context of pharmaceutical inventory system development, along with the integration of real-time reporting and stock alert features as a form of novelty. This system is expected to serve as an innovative solution to enhance inventory management efficiency in the pharmaceutical industry, particularly at PT. Mega Esa Farma.